The Celtic Tiger: Ireland’s Economic Success Story - McGowan, Kieran (Maine Policy Review, 2000)
Roughly 40 years ago, Ireland was described as “just one big farm.” Today, Ireland is the second only to the United States in software exports. Over the past five years, Ireland has experienced an average Gross Domestic Product growth more than double than that of any other country in Europe and record low inflation levels. Such growth has not been accidental. As Kieran McGowan notes in his keynote address at the June 14, 1999 Maine Governor’s Economic Development Conference, four key factors have aided Ireland’s transformation: a young and highly educated workforce; an aggressive and well-funded inward investment program; European Union transfers; and a partnership approach to economic planning. McGowan’s address also emphasizes how Maine might learn from Ireland’s economic success story. Indeed, as a largely rural country, Ireland is challenged by its own “Two Maines” problem and a steady decline in its traditional industries. In describing Ireland’s approach to tackling such issues, McGowan suggests Maine.
Keywords: Ireland economy